2014
DOI: 10.1159/000358670
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Knockdown Inhibits av,�3Integrin-Induced Cell Migration and Invasion and Promotes Apoptosis of Breast Cancer Cells by Inducing Autophagy and Inactivating the PI3K/Akt/mTOR Pathway

Abstract: Background: Osteopontin (OPN) is associated with tumor formation, progression and metastasis, and increased OPN levels have been associated with poor survival in breast cancer. We investigated the mechanisms responsible for OPN activity, and the relationships between OPN expression and clinical parameters in breast cancer. Methods: OPN mRNA and protein levels were compared in malignant and benign breast tumors by polymerase chain reaction (PCR) and immunohistochemistry, respectively, and levels in breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 46 publications
(46 reference statements)
6
50
0
Order By: Relevance
“…Consistent with our finding, Zhang et al [30] observed that knocking down osteopontin, the main ligand of integrin, resulted in downregulation of β 3 -integrin and elevated the expression of LC3-II and Beclin-1 in MDA-MB-231 cells. Inhibiting the function of integrin causes decreased autophagosome formation in starved prostate epithelial cells [31].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our finding, Zhang et al [30] observed that knocking down osteopontin, the main ligand of integrin, resulted in downregulation of β 3 -integrin and elevated the expression of LC3-II and Beclin-1 in MDA-MB-231 cells. Inhibiting the function of integrin causes decreased autophagosome formation in starved prostate epithelial cells [31].…”
Section: Discussionsupporting
confidence: 93%
“…The PI3K/Akt/mTOR signaling pathway promotes cellular growth, migration, protein synthesis, survival and metabolism in response to growth factors and nutrient availability (8). PI3K activates Akt, which leads to the phosphorylation of mTOR via a number of regulators (17).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, B-cell lymphoma-2 (Bcl-2) can promote the proliferation of MCF-7 cells, an effect that is associated with the inhibition of autophagy (7). In addition, a previous study demonstrated that inhibition of the phosphoinositide 3-kinase (PI3K)/RAC-α serine-threonine-protein kinase (Akt)/mammalian target of rapamycin (mTOR) signaling pathway inhibits MDA-MB-231 cell proliferation, and that the PI3K/Akt/mTOR cascade is a key signaling pathway that regulates autophagy (8).…”
Section: Introductionmentioning
confidence: 99%
“…mTOR is suggested to promote fibrogenesis through promotion of proliferation and trans-differentiation of HSCs into myo fibroblast-like cells [44]. Also, recent studies linked mTOR to the signaling pathway of the α V β 3 integrin, a receptor for vitronectin, which is the primary molecule required for fibroblast attachment and spreading [45]. Another possible mechanism that promotes liver fibrosis progression is the development of hepatic steatosis [46].…”
Section: Discussionmentioning
confidence: 99%